A clockwork orange: The subject’s dissolution in modern society - Román González, Viviana (Unaciencia, Revista de Estudios e Investigaciones, 2014)
The Anthony Burgess’ most famous work, A Clockwork Orange, was written in 1962. The great tale of the young “droog” Alex and his large histories of mugging people, beating up other gangs, raping women, and stealing from shops each night are the best reflection of Burgess constant preoccupation about the destructive and self-destructive aspects of men and society. Immortalized ten years after its publication by the excellent Stanley Kubrick’s filmic version, A Clockwork Orange is a strong critic to the modern society which tries to eliminate all the undesirable characteristics of its subjects by using technological practices that, in fact, castrate their free will, their creativity.